Development of conceptual provisions for implementing innovative technologies to quality standards of public passenger transport - Novikova, Alla; Velisevych, Mykola; Poberezhna, Zarina; Symonenko, Roman; Dehtiar, Zoia (Eastern-European Journal of Enterprise Technologies, 2024)
This paper reports a study of the main principles for the formation of public passenger transport service quality standards. The object of the research is public passenger transport services. The task of the study is the development of conceptual foundations for the formation of quality standards using modern innovative technologies. It has been established that the main factor in achieving the quality of public passenger transport services is taking into account innovative technologies and compliance with the criteria and norms of EU standards. Features in the functioning of public passenger transport in the world have been studied, including the use of information platforms for tracking the movement of transport routes, Internet applications, ensuring safety and compliance with environmental requirements. The criteria that serve as indicators of improving the efficiency of the quality of services have been defined, among the main ones are the availability of transportation, comfort, frequency of traffic, and waiting time, quality of service, as well as safety. A system of forming the quality of public passenger transport services has been proposed, which involves determining the needs and requirements of consumers of public passenger transport services, ensures the development of measures to improve the quality of services and their certification. A comprehensive approach to the formation of the quality of public passenger transport services based on the introduction of innovative technologies has been formed, which could make it possible to determine the level of their innovative development, as well as ways to improve it. This approach takes into account the relationship between implemented measures, measuring the level of service quality and the distribution of obligations to ensure the level of services determined by quality criteria. This makes it possible to determine the required level of quality of public passenger transport services and to form a relationship between the level of innovative technologies and the stages of the approach. The practical significance of the results is the design of tools that would ensure the improvement of the quality of public passenger transport services.